Santa's slay [videorecording (DVD)]. - Goldberg, Bill; Culp, Robert; Smith, Douglas; 1930-2010; 1966- (Lions Gate Entertainment, 2005)
"It turns out that Santa Claus is not really the sweet old fellow that we all know and love. In fact, he's a devil and the only thing that's kept his bad side in check was a bet he lost with an angel. After 1000 years of playing nice, the bet is up and Santa is about to open up a can of holiday Whoop-Ass! The only glimmer of hope comes from an old man with a secret, his grandson and his girlfriend. Brace yourself for one really bad santa, bent on spreading holiday fear."--Container.